Utilizing appropriate technology dry seasoning mixing and sealing machines to increase productivity of cassava chips business - Dino Caesaron; Sheila Amalia Salma; Farell Ardani; Faisal Muhammad Nasution; Murman Dwi Prasetio (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2023)
Sukapura Village, located in Bandung Regency, has a Family Welfare Empowerment (PKK) program that includes various activities, such as the production of cassava chips. Currently, there is a high demand for cassava chips that cannot be met. Through analysis conducted by the community service team, it has been determined that the demand for cassava chips exceeds the production capacity. One of the contributing factors is the manual process involved in making cassava chips, which takes a relatively long time. One specific manual process is the mixing of cassava chips with dry seasoning. The cassava chips are placed in a container, and then dry spices are added. The mixing process is carried out by hand, ensuring that the spices are evenly distributed throughout the cassava chips. This manual process typically takes around 10-14 minutes for every 1.5 kg of cassava chips. To address this issue and improve efficiency, the community service team has designed and constructed a machine specifically for mixing dry seasoning. With this machine, the mixing process is significantly more efficient, taking less than 5 minutes to achieve optimal results. As a result, the time efficiency and productivity of the mixing process have greatly increased.